1997
DOI: 10.1002/jor.1100150216
|View full text |Cite
|
Sign up to set email alerts
|

Contact pressure and tension in anterior cruciate ligament grafts subjected to roof impingement during passive extension

Abstract: Contact between an anterior cruciate ligament graft and the intercondylar roof has been termed roof impingement. Grafts with impingement sustain permanent damage, and if the injury is extensive enough, then the graft may fail, causing recurrent instability. This study evaluated two mechanical factors that could be responsible for the graft injury associated with roof impingement: an increase in graft tension or elevated pressures between the graft and the roof, or both. An anterior cruciate ligament reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 26 publications
0
53
1
Order By: Relevance
“…Our study also found that the mean ACL graft forces were higher than the ACL forces at each flexion angle (significantly higher at 15° of flexion), even though the anterior tibial translation measured in the reconstructed knee was slightly larger than the translation of the intact knee. The difference in force between the ACL and graft measured in this study was not as large as those reported in the literature (Grontvedt et al 1996, Markolf et al 1996, Goss et al 1997. This may be due to the differences in surgical techniques used in these studies.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Our study also found that the mean ACL graft forces were higher than the ACL forces at each flexion angle (significantly higher at 15° of flexion), even though the anterior tibial translation measured in the reconstructed knee was slightly larger than the translation of the intact knee. The difference in force between the ACL and graft measured in this study was not as large as those reported in the literature (Grontvedt et al 1996, Markolf et al 1996, Goss et al 1997. This may be due to the differences in surgical techniques used in these studies.…”
Section: Discussioncontrasting
confidence: 62%
“…In previous studies, ACL graft forces were measured when the anterior tibial translation was matched to that of the intact knee under an anterior tibial load at 30° of flexion (Markolf et al 1996, Goss et al 1997). These graft forces were dramatically increased compared to the ACL forces under the anterior tibial load.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have conducted displacement (Beynnon et al, 1992) or tension (Goss et al, 1997;Markolf et al, 1990;Goss et al, 1997) measurements of the ACLs or ACL substitutes. However, no study used the data to determine the redirecting forces that are caused by the angulation of the graft at the entrance of the bone tunnels.…”
Section: Article In Pressmentioning
confidence: 99%
“…Roof impingement disturbs the function of the knee because the contact pressure increases between the graft and the roof, which occurs prematurely before the knee reaches maximum hyperextension. 4 The premature increase in contact pressure causes symptoms of either a loss of extension or an increase in anterior laxity. 8,9,13 Avoiding roof impingement requires an understanding that the placement of the tibial tunnel in the sagittal plane determines whether the ACL graft impinges against the roof during extension.…”
Section: Definition Symptoms and Avoidance Of Roof Impingementmentioning
confidence: 99%